Two new species of the genus Daptonema Cobb, 1920 (Nematoda: Xyalidae) found in the monospecific Halophila ovalis patches within an intertidal mixed-species seagrass bed on the coast of the Andaman Sea, Thailand - Aryuthaka, Chittima; Kito, Kenji (Zootaxa, 2012)
Daptonema hyalocella sp. n. and D. setihyalocella sp. n. are described from the Ban Pa Khlok seagrass bed, Phuket Prov-ince, Thailand. These new species are characterized by the epidermal chords consisting of large cells with a transparentappearance, as in D. conicum (Filipjev, 1922) and D. trabeculosum (G. Schneider, 1906). The key characteristics of D.hyalocella sp. n. are the peculiar epidermal chords, loose S-shaped spicules with no proximal cephalation, an indistinctgubernaculum with a lateral piece, and two terminal setae. For D. setihyalocella sp. n., the key characteristics are similarpeculiar epidermal chords, but in this case with the L-shaped spicules having proximal cephalation, a distinct gubernaculum with dorsal apophysis and lateral piece, and four terminal setae.